Electromagnetic shielding film and preparation method and application thereof

By using polyvinyl alcohol-water-multi-wall carbon nanotube mixed materials and liquid metal gallium indium alloy nanoparticles, the problem of limited intelligent development of electromagnetic shielding materials in the prior art is solved, and the intelligent response to electromagnetic shielding performance and simplification of the preparation process is achieved.

CN119570183AActive Publication Date: 2025-03-07NANJING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411878397.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The development of existing electromagnetic shielding materials in the direction of intelligence is limited, the preparation process is complex and the performance is fixed, and the intelligent response to electromagnetic shielding performance cannot be achieved.

Method used

The mixed polyvinyl alcohol-water-multi-wall carbon nanotube material is used as the film matrix, and liquid metal gallium indium alloy nanoparticles are added as functional filler. An electromagnetic shielding film is prepared through casting, constant temperature and humidity locking treatment and force-controlled induction treatment.

Benefits of technology

It realizes the intelligent response characteristics of electromagnetic shielding films, and can flexibly adjust its own electromagnetic shielding parameters when the application scenario changes, adapt to different performance requirements, and simplifies the preparation process and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570183A_ABST
    Figure CN119570183A_ABST
Patent Text Reader

Abstract

The invention provides an electromagnetic shielding film. The electromagnetic shielding film adopts a polyvinyl alcohol-water-multi-walled carbon nanotube mixed material as a film substrate, and adopts liquid metal gallium indium alloy nanoparticles as a functional filler; the liquid metal gallium indium alloy nanoparticles are embedded in the lower part of the thin film substrate and are stacked to form a functional filler layer. The electromagnetic film sample has excellent electromagnetic shielding performance, also has the advantages of flexibility, plasticity and strong mechanical performance, and can fully adapt to various use environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic shielding composite materials, and in particular to an electromagnetic shielding film and a preparation method and application thereof. Background Art

[0002] In recent years, the rapid development of information technology has promoted the continuous upgrading of military communication systems, and the application of electromagnetic shielding materials in the military field has become more and more extensive. Electromagnetic shielding materials are a technical means to eliminate the adverse effects of electromagnetic waves by cutting off the propagation path of electromagnetic waves. By covering the surface of weapons and equipment with electromagnetic shielding materials, electromagnetic waves can be effectively blocked and absorbed, reducing the damage of electromagnetic pulses to equipment. In addition, similar to command cabins, which are the "brains" and "nerve centers" for coordinating joint operations of various ground arms during wartime, the application of electromagnetic shielding materials can achieve signal filtering and isolation, ensuring the survivability of command and control systems. Faced with the increasingly complex battlefield environment, electromagnetic shielding materials are required to gradually develop in the direction of lightweight and intelligent. Metal, as a traditional electromagnetic shielding material, has excellent electrical conductivity. However, due to the defects of metal materials such as high mass density, fixed performance parameters, and inconvenient processing and manufacturing, the development of intelligent electromagnetic shielding materials is limited.

[0003] CN 118076077A discloses a multifunctional flexible electromagnetic shielding film product and a preparation method thereof. The structure of the electromagnetic shielding film includes a super hydrophobic layer, a transition layer, an absorption layer and a reflection layer from top to bottom. The film is prepared layer by layer by vacuum filtration, and then dried, separated, and hot pressed, and finally sprayed to prepare a super hydrophobic layer to obtain a multifunctional flexible electromagnetic shielding film product. The film product dopant includes fluorinated silicon dioxide nanoparticles, bacterial cellulose, and carbon nanotubes coated with ferroferric oxide, etc. The number of materials used is large and complex, and the preparation process is cumbersome. The film product has fixed performance and cannot achieve intelligent response of electromagnetic shielding performance. CN118110028A discloses a multi-layer structure of flexible super hydrophobic high absorption electromagnetic shielding composite film and a preparation method thereof. It is a silver nanowire-polyurethane fiber film prepared by traditional electrospinning technology. The electromagnetic shielding composite film is flexible and lightweight, and has a "absorption-reflection-reabsorption" multi-layer structure shielding mechanism, but the preparation process is relatively complicated, the electromagnetic shielding efficiency is up to 54 dB, and the intelligent response of electromagnetic shielding performance cannot be achieved. Summary of the invention

[0004] In order to make up for the defects of the prior art, the present invention provides an electromagnetic shielding film, wherein the electromagnetic shielding film adopts a polyvinyl alcohol-water-multi-walled carbon nanotube mixed material as a film matrix, and adopts liquid metal gallium indium alloy nanoparticles as a functional filler; the liquid metal gallium indium alloy nanoparticles are embedded in the lower part of the film matrix and stacked to form a functional filler layer; the liquid metal gallium indium alloy nanoparticles are added to a polyvinyl alcohol-water-multi-walled carbon nanotube suspension in a mass ratio of (1-5):26 and mixed evenly, and then the electromagnetic shielding film is obtained by casting, constant temperature and humidity water locking treatment, and force-controlled induction treatment; In terms of mass percentage, the water content of the electromagnetic shielding film is 20-25%; the thickness of the functional filler layer is 1 / 10-1 / 3 of the thickness of the electromagnetic shielding film; and the particle size of the liquid metal gallium-indium alloy nanoparticles is 1-5µm.

[0005] Preferably, the mass ratio of polyvinyl alcohol, multi-walled carbon nanotubes and liquid metal gallium-indium alloy nanoparticles in the electromagnetic shielding film is 5: (0.05-0.2): (1-5).

[0006] Preferably, the liquid metal gallium-indium alloy nanoparticles are prepared by dispersing the liquid metal gallium-indium alloy in ethanol and then removing the ethanol by centrifugation; in terms of mass percentage, the liquid metal gallium-indium alloy contains 75.5% of metal gallium and 24.5% of metal indium.

[0007] Preferably, the multi-walled carbon nanotubes have a diameter of 5 to 50 nm and a length of 5 to 20 µm.

[0008] The present invention also provides a method for preparing an electromagnetic shielding film, the preparation method comprising adding liquid metal gallium-indium alloy nanoparticles to a polyvinyl alcohol-water-multi-walled carbon nanotube suspension in a mass ratio of (1-5):26 and mixing them evenly, and then subjecting the film to casting, constant temperature and humidity water locking treatment, and force-controlled induction treatment to obtain the electromagnetic shielding film; The constant temperature and humidity water-locking treatment is to place the film product obtained by casting in an environment with a temperature of 20-30°C and a humidity of 60% to dehydrate it to a moisture content of 20-25%; the force-controlled induction treatment is to uniaxially stretch the film obtained by the constant temperature and humidity water-locking treatment to 120-240% of the original length.

[0009] Preferably, the liquid metal gallium-indium alloy is prepared by mixing metal gallium and metal indium in a mass ratio of 75.5:24.5 and then heating at 60° C. for 1 hour.

[0010] Preferably, the polyvinyl alcohol-water-multi-walled carbon nanotube suspension is prepared by adding polyvinyl alcohol to water, mixing uniformly at 90-98° C., and then adding multi-walled carbon nanotubes; the mass ratio of the polyvinyl alcohol, water, and multi-walled carbon nanotubes is 5:20:(0.05-0.2).

[0011] Further preferably, the preparation steps are: Step 1, adding polyvinyl alcohol to water, heating to 95° C. and stirring evenly after mixing, and then adding multi-walled carbon nanotubes to obtain a polyvinyl alcohol-water-multi-walled carbon nanotube suspension; the mass ratio of the polyvinyl alcohol, water, and multi-walled carbon nanotubes is 5:20:0.2; Step 2, dispersing the liquid metal gallium-indium alloy into ethanol, centrifuging at a speed of 4000 rpm for 20 minutes, and separating the ethanol to obtain liquid metal gallium-indium alloy nanoparticles; the metal gallium-indium alloy is prepared by mixing metal gallium and metal indium in a mass ratio of 75.5:24.5 and then heating at 60° C. for 1 hour; the particle size of the liquid metal gallium-indium alloy nanoparticles is 1-5 μm; Step 3, adding the liquid metal gallium-indium alloy nanoparticles prepared in step 2 to the polyvinyl alcohol-water-multi-walled carbon nanotube suspension prepared in step 1 at a mass ratio of 5:25.2, mixing evenly, and transferring to a film-forming mold for casting; Step 4, placing the film obtained by casting in step 3 in an environment with a constant temperature of 20-30° C. and a constant humidity of 60% to dehydrate the film to a moisture content of 20-25%; The method for determining the water content is as follows: first, weigh and record the mass of the forming mold (polytetrafluoroethylene mold), then weigh the total mass of the mold and the film after casting in step 3, and the change in mass before and after the two is the mass of the film at the determined time; secondly, calculate the mass of the film when the water content is 20%-25% according to the total mass of the materials fed in steps 1-3 and the mass of water; finally, place the forming mold together with the film on a weighing instrument, peel and weigh in real time, and then perform a constant temperature and humidity water-locking treatment. When the mass displayed by the weighing instrument is consistent with the mass of the film when the water content is 20%-25%, take out the film to obtain a film treated with constant temperature and humidity water-locking treatment; Step 5, uniaxially stretching the film obtained in step 4 to 230-235% of the original length, and / or reducing the thickness to 40-50% of the original thickness, to obtain an electromagnetic shielding film.

[0012] The electromagnetic shielding film obtained by the technical solution of the present invention is applied to electromagnetic shielding of electronic devices.

[0013] Preferably, the electromagnetic shielding film is subjected to force-controlled induction treatment and then applied to electronic shielding of electronic devices. The electromagnetic shielding film obtained by the technical solution of the present invention has the characteristics of intelligent response after film formation, and can flexibly adjust its own electromagnetic shielding parameters to adapt to different performance requirements when the application scenario changes. Here, intelligent response refers to the electromagnetic shielding film being subjected to force-controlled stretching treatment again according to different performance requirements to change the characteristics of its electromagnetic shielding parameters.

[0014] Beneficial effects: Compared with the prior art, the advantages of the present invention are: 1. The preparation process is simple, without complicated operations, and the size of the prepared samples is only affected by the sample mold, which can achieve mass preparation of samples.

[0015] 2. The polyvinyl alcohol matrix does not completely lose water during the film-forming stage. Under the premise of having considerable mechanical strength, the water content of 20% to 25% ensures that the inside of the film is in a solid-liquid intermediate phase; the intermediate phase can not only ensure the film forming, but also does not limit the fluidity of the liquid metal gallium indium alloy, so that it can be deformed at will under tension, connect multi-walled carbon nanotubes, dynamically adjust the construction of the conductive network, and realize the intelligent response of electromagnetic shielding performance.

[0016] 3. The film sample has excellent electromagnetic shielding performance, and has the advantages of flexibility, plasticity and strong mechanical properties, and can fully adapt to a variety of usage environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the force-controlled induction process of the electromagnetic shielding film prepared in Example 1.

[0018] Figure 2 This is the surface morphology of the electromagnetic shielding film prepared in Example 1.

[0019] Figure 3 This is the bottom surface morphology of the electromagnetic shielding film prepared in Example 1.

[0020] Figure 4 This is a schematic cross-sectional view of the electromagnetic shielding film prepared in Example 1 before force-controlled induction.

[0021] Figure 5 This is a schematic cross-sectional view of the electromagnetic shielding film prepared in Example 1 after force-controlled induction.

[0022] Figure 6 The performance changes of the electromagnetic shielding film prepared in Example 1 before and after force-controlled induction.

[0023] Figure 7~Figure 11The electromagnetic shielding performance parameter diagrams of the films prepared in Example 1 with lengths of 3 cm, 4 cm (stretched length of 1 cm), 5 cm (stretched length of 2 cm), 6 cm (stretched length of 3 cm), and 7 cm (stretched length of 4 cm) are shown in sequence. DETAILED DESCRIPTION

[0024] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.

[0025] Embodiment 1: Step 1, adding 5g of polyvinyl alcohol to 20ml of water (mass 20g), heating to 95°C after mixing, and mechanically stirring for 10h to obtain a mixed solution at a stirring speed of 700rpm; then adding 0.2g of multi-walled carbon nanotubes to the mixed solution to obtain a polyvinyl alcohol-water-multi-walled carbon nanotube suspension; Step 2, dispersing the liquid metal gallium indium alloy in anhydrous ethanol and ultrasonically dispersing it for 20 minutes to obtain an ethanol solution of liquid metal gallium indium alloy nanoparticles; centrifuging the obtained ethanol solution of liquid metal gallium indium alloy nanoparticles at a speed of 4000 rpm for 20 minutes, and obtaining liquid metal gallium indium alloy nanoparticles after separating ethanol; the liquid metal gallium indium alloy is prepared by mixing metal gallium and metal indium in a mass ratio of 75.5:24.5 and then heating at 60°C for 1 hour; Step 3, taking 0.2 g of the liquid metal gallium indium alloy nanoparticles prepared in step 2, adding them to the polyvinyl alcohol-water-multi-walled carbon nanotube suspension prepared in step 1 and mixing them evenly, degassing the solution and transferring it to a molding mold (polytetrafluoroethylene mold) for casting; the sample thickness inside the mold is 1.0 mm; Step 4, after the sample obtained in step 3 is cooled to room temperature, a constant temperature and humidity water-locking treatment is performed, wherein the constant temperature and humidity water-locking treatment is to place the sample in an environment of a constant temperature of 20-30° C. and a constant humidity of 60% to dehydrate the sample to a water content of 20-25%; the obtained film has a thickness of 1.0 mm, a length of 3.0 cm, and a width of 2.0 cm; The method for determining the water content is as follows: first, weigh and record the mass of the forming mold (polytetrafluoroethylene mold), then weigh the total mass of the mold and the film after casting in step 3, and the change in mass before and after is the mass of the film at the determined moment; secondly, calculate the mass of the film when the water content is 20% to 25% according to the total mass of the feed in steps 1 to 3 and the mass of water; finally, place the forming mold together with the film on a weighing instrument, peel and weigh in real time, and then perform a constant temperature and humidity water-locking treatment. When the mass displayed by the weighing instrument is consistent with the mass of the film when the water content is 20% to 25%, take out the film to obtain a film treated with constant temperature and humidity water-locking treatment; Step 5, subjecting the film obtained in step 4 to a force-controlled induction treatment, wherein the force-controlled induction treatment is to use a force-controlled induction film stretching platform to uniaxially stretch the film obtained in step 4 to 120-240% of the original length, at which point the thickness is reduced to 40-50% of the original thickness, thereby obtaining an electromagnetic shielding film. There is a length scale at the bottom of the stretching platform, and the stretching of the film can be observed. The initial length of the electromagnetic shielding film is 3.0 mm, and the single film stretching length is set to 1.0 cm, until it is stretched to 7.0 cm to reach the film limit (after multiple tests, the film will be in a state of easy breakage when further stretched), and electromagnetic shielding films with lengths of 3 cm, 4 cm (stretching length is 1 cm), 5 cm (stretching length is 2 cm), 6 cm (stretching length is 3 cm), and 7 cm (stretching length is 4 cm, and the thickness of the film is measured to be 0.5 mm at this time); Figure 1 The process of uniaxial force-controlled induced stretching of the prepared electromagnetic shielding film was demonstrated. After multiple tests, the film obtained the best electromagnetic shielding performance when it was stretched to 200%~240% of its initial length. If it was further stretched, the film would be in a state of easy fracture and would not have the electromagnetic shielding function. Figure 2 , 3 They are respectively the surface morphology and the bottom morphology of the electromagnetic shielding film prepared in this embodiment; Figure 4 is a schematic cross-sectional view of the initial state of the electromagnetic shielding film prepared in this embodiment, where the thickness of the functional filler layer is 1 / 10 to 1 / 8 of the thickness of the electromagnetic shielding film; Figure 5 : is a schematic cross-sectional view of the electromagnetic shielding film prepared in this embodiment when it is stretched to 240% of the initial length by force control. At this time, the thickness of the functional filler layer is 1 / 4 to 1 / 3 of the thickness of the electromagnetic shielding film. The electromagnetic shielding performance of the electromagnetic shielding film before and after the force control stretching is tested. The test results are as follows: Figure 6 As shown, the electromagnetic shielding performance increases from 7~8dB to 45~48dB.

[0026] Measuring electromagnetic shielding performance The electromagnetic shielding performance of the films with lengths of 3 cm, 4 cm (stretched length of 1 cm), 5 cm (stretched length of 2 cm), 6 cm (stretched length of 3 cm), and 7 cm (stretched length of 4 cm) in step 6 was measured; the electromagnetic shielding parameters obtained through testing were 7.55 dB, 15.21 dB, 24.01 dB, 33.96 dB, and 46.11 dB, respectively.

[0027] The electromagnetic shielding films of lengths of 3 cm, 4 cm (stretched length of 1 cm), 5 cm (stretched length of 2 cm), 6 cm (stretched length of 3 cm), and 7 cm (stretched length of 4 cm, the thickness of the film at this time is measured to be 0.5 mm) prepared in Example 1 are used as measurement objects, and the process of electromagnetic shielding performance testing and the process of obtaining electromagnetic shielding performance parameters (corresponding to 7.55 dB, 15.21 dB, 24.01 dB, 33.96 dB, and 46.11 dB, respectively) are illustrated by way of example; (1) Introduction to electromagnetic shielding performance characterization parameters: Electromagnetic shielding materials usually achieve the shielding effect of electromagnetic waves through three shielding mechanisms. What is reflected on the surface of the material is the reflection loss SE R , what is attenuated in the material is the absorption loss SE A , and the multiple reflection loss is often ignored. The electromagnetic shielding performance of materials is evaluated by electromagnetic shielding effectiveness, which is measured in decibels (dB), so shielding efficiency is equal to SE R +SE A ; (2) Introduction to the electromagnetic shielding test process: The electromagnetic shielding performance of the material is tested by a vector network analyzer. For thin-film materials, the waveguide method is used to test the S parameters of the material in different bands and calculate the electromagnetic shielding effectiveness of the material. Usually, the waveguide method is used to test the S parameters of materials, and four groups of data can be obtained, namely S11, S21, S22, and S12. The first subscript number means the receiving port, and the second subscript number means the transmitting port. For example, S21 means that port 1 transmits the signal and port 2 receives the signal. Therefore, when calculating the electromagnetic shielding effectiveness of materials, S11 and S21 are usually calculated as a group, and S22 and S12 are calculated as a group; The electromagnetic shielding film prepared in Example 1 was subjected to force-controlled stretching treatment to obtain electromagnetic shielding films with lengths of 3 cm, 4 cm (stretched length of 1 cm), 5 cm (stretched length of 2 cm), 6 cm (stretched length of 3 cm), and 7 cm (stretched length of 4 cm, and the thickness of the film was measured to be 0.5 mm); Then the electromagnetic shielding test was carried out respectively, and S was measured according to the vector network analysis. 11 , S 21 , and then the computer calculates formula 1 and formula 2 together to get Figures 7 to 11The SE parameters and P parameters shown in the figure are used to calculate the SE data ( Figure 7 P R , P T , P A Parameters and SE A , SE R The parameters correspond to the electromagnetic shielding film with a length of 3 cm obtained in Example 1, and the calculated SE is 7.55 dB; Figure 8 P R , P T , P A Parameters and SE A , SE R The parameters correspond to the electromagnetic shielding film with a length of 4 cm obtained in Example 1, and the calculated SE is 15.21 dB; Fig. 9 P R , P T , P A Parameters and SE A , SE R The parameters correspond to the electromagnetic shielding film with a length of 5 cm obtained in Example 1, and the calculated SE is 24.01 dB, Fig.10 P R , P T , P A Parameters and SE A , SE R The parameters correspond to the electromagnetic shielding film with a length of 6 cm obtained in Example 1, and the calculated SE is 33.96 dB; Fig.11 The PR, PT, PA parameters and SEA, SER parameters correspond to the electromagnetic shielding film with a length of 7 cm obtained in Example 1, and the calculated SE is 46.11 dB). The data show that the electromagnetic shielding film prepared by the present invention has good intelligent response characteristics, and can flexibly adjust its own electromagnetic shielding parameters to adapt to different performance requirements when the application scenario changes. Intelligent response here means that the prepared electromagnetic shielding film is subjected to force-controlled stretching treatment again according to different performance requirements to obtain gradient electromagnetic shielding parameters (7.55 dB, 15.21 dB, 24.01 dB, 33.96 dB, and 46.11 dB, respectively) to adapt to different scenario requirements.

[0028] Embodiment 2: The other processes are the same as in Example 1, except that: in step 2, 3 g of liquid metal gallium indium alloy is added. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which is 5.18 dB and 35.19 dB respectively. Before force-controlled stretching mentioned here refers to when the electromagnetic shielding film is at the initial length, and after force-controlled stretching mentioned here refers to when it is stretched to 7.0 cm. The following Examples 3 to 8; Comparative Examples 2 to 3 are understood in the same way.

[0029] Embodiment 3: The other processes are the same as those in Example 1, except that 3 g of liquid metal gallium-indium alloy is added in step 2. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which are 5.18 dB and 35.19 dB, respectively.

[0030] Embodiment 4: The other processes are the same as in Example 1, except that 2 g of liquid metal gallium-indium alloy is added in step 2. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which are 4.99 dB and 22.96 dB, respectively.

[0031] Embodiment 5: The other processes are the same as in Example 1, except that: in step 2, 1 g of liquid metal gallium-indium alloy is added. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which are 5.05 dB and 16.57 dB, respectively.

[0032] Embodiment 6: The other processes were the same as in Example 1, except that: in step 1, 0.15 g of multi-walled carbon nanotubes were added. The electromagnetic shielding performance before and after force-controlled stretching was recorded, which were 6.41 dB and 32.67 dB, respectively.

[0033] Embodiment 7: The other processes are the same as in Example 1, except that: in step 1, 0.10 g of multi-walled carbon nanotubes is added. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which are 6.39 dB and 30.54 dB, respectively.

[0034] Embodiment 8: The other processes are the same as in Example 1, except that: in step 1, 0.05 g of multi-walled carbon nanotubes are added. The electromagnetic shielding performance before and after force-controlled stretching is recorded, which are 6.49 dB and 28.72 dB, respectively.

[0035] Comparative Example 1: The other processes are the same as in Example 1, in order to determine the internal phase relationship of the electromagnetic shielding film and compare the performance changes of the film under different water contents. In step 5, the sample is placed in a constant temperature and humidity chamber for 24 hours before the preparation is completed. At this time, the water content of the sample is 50%, but the water content is too high to form a film.

[0036] Comparative Example 2: The other processes are the same as in Example 1, except that in step 5, the sample is placed in a constant temperature and humidity chamber for 96 hours before the preparation is completed. At this time, the moisture content of the sample is 0%, and the electromagnetic shielding properties of the film before and after force-controlled stretching are 6.89 dB and 7.01 dB, which are basically unchanged.

[0037] Comparative Example 3: The other processes are the same as in Example 1, except that the polyvinyl alcohol matrix in step 1 is replaced with PDMS (polydimethylsiloxane) material. The specific operation is as follows: 25 g of PDMS is weighed, and then 2.5 g of ligand is added thereto to obtain a mixed solution. In step 4, the solution is degassed and then drooled in a horizontally placed polytetrafluoroethylene mold. The sample thickness in the mold is 1.0 mm. After being placed in an oven and heated at 60°C for 1 h, an electromagnetic shielding film is prepared. The electromagnetic shielding performance of the film before and after force-controlled stretching is 7.15 dB and 7.09 dB, which is basically unchanged.

[0038] It should be noted that, although the above embodiments have been described in this article, the patent protection scope of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the patent protection scope of the present invention.

Claims

1. An electromagnetic shielding film, characterized in that: The electromagnetic shielding film adopts a polyvinyl alcohol-water-multi-walled carbon nanotube mixed material as a film matrix, and adopts liquid metal gallium indium alloy nanoparticles as a functional filler; the liquid metal gallium indium alloy nanoparticles are embedded in the lower part of the film matrix and stacked to form a functional filler layer; the liquid metal gallium indium alloy nanoparticles are added to the polyvinyl alcohol-water-multi-walled carbon nanotube suspension according to a mass ratio of liquid metal gallium indium alloy nanoparticles: polyvinyl alcohol-water-multi-walled carbon nanotube suspension = (1-5): 26, and the mixture is evenly mixed, and then the electromagnetic shielding film is obtained by casting, constant temperature and humidity water locking treatment, and force control induction treatment; In terms of mass percentage, the water content of the electromagnetic shielding film is 20-25%; the thickness of the functional filler layer is 1 / 10-1 / 3 of the thickness of the electromagnetic shielding film; and the particle size of the liquid metal gallium-indium alloy nanoparticles is 1-5µm.

2. The electromagnetic shielding film according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, multi-walled carbon nanotubes and liquid metal gallium-indium alloy nanoparticles in the electromagnetic shielding film is 5: (0.05-0.2): (1-5).

3. The electromagnetic shielding film according to claim 1, characterized in that: The liquid metal gallium-indium alloy nanoparticles are prepared by dispersing the liquid metal gallium-indium alloy in ethanol and then removing the ethanol by centrifugation; the liquid metal gallium-indium alloy contains 75.5% of metal gallium and 24.5% of metal indium by mass; the multi-walled carbon nanotubes have a diameter of 5 to 50 nm and a length of 5 to 20 µm.

4. The electromagnetic shielding film according to claim 1, characterized in that: The constant temperature and humidity water-locking treatment is to place the film product obtained by casting in an environment with a temperature of 20-30°C and a humidity of 60% to dehydrate it to a moisture content of 20-25%; the force-controlled induction treatment is to uniaxially stretch the film obtained by the constant temperature and humidity water-locking treatment to 120-240% of the original length.

5. A method for preparing an electromagnetic shielding film, characterized in that: Liquid metal gallium-indium alloy nanoparticles are added into a polyvinyl alcohol-water-multi-walled carbon nanotube suspension in a mass ratio of (1-5):26 and mixed evenly, and then subjected to casting, constant temperature and humidity water locking treatment, and force-controlled induction treatment to obtain the electromagnetic shielding film; The constant temperature and humidity water-locking treatment is to place the film product obtained by casting in an environment with a temperature of 20-30°C and a humidity of 60% to dehydrate it to a moisture content of 20-25%; the force-controlled induction treatment is to uniaxially stretch the film obtained by the constant temperature and humidity water-locking treatment to 120-240% of the original length.

6. The preparation method according to claim 5, characterized in that: The liquid metal gallium-indium alloy is prepared by mixing metal gallium and metal indium in a mass ratio of 75.5:24.5 and then heating at 60° C. for 1 hour.

7. The preparation method according to claim 5, characterized in that: The polyvinyl alcohol-water-multi-walled carbon nanotube suspension is prepared by adding polyvinyl alcohol to water, mixing uniformly at 90-98° C., and then adding multi-walled carbon nanotubes; the mass ratio of the polyvinyl alcohol, water, and multi-walled carbon nanotubes is 5:20:(0.05-0.2).

8. The preparation method according to claim 5, characterized in that: The preparation steps are: Step 1, adding polyvinyl alcohol to water, mixing and heating to 95° C. to mix evenly, and then adding multi-walled carbon nanotubes to obtain a polyvinyl alcohol-water-multi-walled carbon nanotube suspension; the mass ratio of the polyvinyl alcohol, water, and multi-walled carbon nanotubes is 5:20:0.2; Step 2, dispersing the liquid metal gallium-indium alloy into ethanol, centrifuging at a speed of 4000 rpm for 20 minutes, and separating the ethanol to obtain liquid metal gallium-indium alloy nanoparticles; the metal gallium-indium alloy is prepared by mixing metal gallium and metal indium in a mass ratio of 75.5:24.5 and then heating at 60° C. for 1 hour; Step 3, adding the liquid metal gallium-indium alloy nanoparticles prepared in step 2 to the polyvinyl alcohol-water-multi-walled carbon nanotube suspension prepared in step 1 at a mass ratio of 5:25.2, mixing evenly, and transferring to a film-forming mold for casting; Step 4, placing the film obtained by casting in step 3 in an environment with a constant temperature of 20-30° C. and a constant humidity of 60% to dehydrate the film to a moisture content of 20-25%; Step 5, uniaxially stretching the film obtained in step 4 to 230-235% of the original length, and / or reducing the thickness to 40-50% of the original thickness, to obtain an electromagnetic shielding film.

9. An application of the electromagnetic shielding film according to claims 1 to 4 or the electromagnetic shielding film prepared by the preparation method according to claims 5 to 8, characterized in that: The electromagnetic shielding film is applied to electromagnetic shielding of electronic devices.

10. The use according to claim 9, characterized in that The electromagnetic shielding film is subjected to force-controlled induction treatment and then applied to electronic shielding of electronic devices.

Citation Information

Patent Citations

  • Flexible super-hydrophobic high-absorption electromagnetic shielding composite film based on multilayer structure and preparation method of flexible super-hydrophobic high-absorption electromagnetic shielding composite film

    CN118110028A

  • Conductive ink as well as preparation method and application thereof

    CN112552745A

  • Liquid metal functional composite film and preparation method thereof

    CN114525002A

  • Flexible multilayer electromagnetic shielding composite film based on liquid metal and preparation method thereof

    CN115666118A

  • Method for preparing of polymer-carbon nanotube composite particles

    KR1020120124611A

Cited By

  • Liquid metal-carbon nanotube doped photosensitive resin and preparation method and application thereof

    CN121086441A